Representing Trauma Through Fragmented Memory in Charlotte Wells' Aftersun (2022): A Caruthian Analysis - Yazid Mishbahul Fikri; Dwi Nur Cahyani Sri Kusumaningtyas (Journal of Cultural Narratives in Digital Society, 2026)
Trauma is often represented in films through memory, emotional distance, and fragmented storytelling rather than direct explanation. This study aims to analyze how trauma is represented through fragmented memory in Charlotte Wells' Aftersun (2022) by using Cathy Caruth's trauma theory. The study applies a qualitative descriptive method with a film studies approach. The primary data source is Aftersun (2022), while the data consists of scenes, dialogues, visual elements, and cinematic techniques related to trauma representation. The data were collected through repeated viewing, note-taking, and scene selection. The analysis focuses on Caruth's concepts of unclaimed experience, belatedness, and repetition. The findings show that trauma in Aftersun (2022) is represented through fragmented memories that gradually reveal emotional meaning. Through the use of camcorder footage, silence, visual repetition, spatial separation, and fragmented editing, the film portrays trauma as an unresolved experience that cannot be fully understood when it occurs. The study also finds that Sophie reconstructs her understanding of her father through retrospective interpretation, allowing traumatic meaning to emerge over time. Therefore, Aftersun (2022) represents trauma not through direct narrative explanation but through fragmented memory and cinematic form.